2019
DOI: 10.1186/s12935-019-1059-8
|View full text |Cite
|
Sign up to set email alerts
|

AGI-134: a fully synthetic α-Gal glycolipid that converts tumors into in situ autologous vaccines, induces anti-tumor immunity and is synergistic with an anti-PD-1 antibody in mouse melanoma models

Abstract: BackgroundTreatments that generate T cell-mediated immunity to a patient’s unique neoantigens are the current holy grail of cancer immunotherapy. In particular, treatments that do not require cumbersome and individualized ex vivo processing or manufacturing processes are especially sought after. Here we report that AGI-134, a glycolipid-like small molecule, can be used for coating tumor cells with the xenoantigen Galα1-3Galβ1-4GlcNAc (α-Gal) in situ leading to opsonization with pre-existing natural anti-α-Gal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Binding of anti-Gal to inserted α-gal glycolipids initiates uptake of tumor cells and cell membranes by APCs, followed by effective activation of tumor-specific CD4 + and CD8 + T cells and destruction of injected tumors and of distant metastases ( Galili et al, 2007 ; Abdel-Motal et al, 2009b ). In subsequent studies, the efficacy of this α-gal therapy was further demonstrated in GT-KO mice with a synthetic α-gal glycolipid called AGI-134 that was injected into B16 lesions ( Shaw et al, 2019 ). In Phase I clinical trials in patients with solid tumors at advanced stages of the disease, intratumoral injection of rabbit RBC α-gal glycolipids was found to be safe with no adverse effects ( Whalen et al, 2012 ; Galili, 2013b ; Albertini et al, 2016 ).…”
Section: Immunological Processes Associated With Anti-gal/α-gal Epitope Interactions Which May Be Harnessed For α-Gal Therapiesmentioning
confidence: 99%
“…Binding of anti-Gal to inserted α-gal glycolipids initiates uptake of tumor cells and cell membranes by APCs, followed by effective activation of tumor-specific CD4 + and CD8 + T cells and destruction of injected tumors and of distant metastases ( Galili et al, 2007 ; Abdel-Motal et al, 2009b ). In subsequent studies, the efficacy of this α-gal therapy was further demonstrated in GT-KO mice with a synthetic α-gal glycolipid called AGI-134 that was injected into B16 lesions ( Shaw et al, 2019 ). In Phase I clinical trials in patients with solid tumors at advanced stages of the disease, intratumoral injection of rabbit RBC α-gal glycolipids was found to be safe with no adverse effects ( Whalen et al, 2012 ; Galili, 2013b ; Albertini et al, 2016 ).…”
Section: Immunological Processes Associated With Anti-gal/α-gal Epitope Interactions Which May Be Harnessed For α-Gal Therapiesmentioning
confidence: 99%
“…A Phase 1/2 trial of AGI-134 is currently recruiting patients, and trials of IMM60 are anticipated. 79 81 IFx-Hu2.0 is a plasmid DNA encoding the streptococcal membrane protein, Emm55, and the first in human Phase 1 study of intratumoural use in melanoma is in progress. 82 Preliminary laboratory data from the first three patients in the trial suggest the treatment may be associated with decreases in tumour cells and formation of an immune response.…”
Section: Novel Agents In Development For Unresectable and Metastatic mentioning
confidence: 99%
“…Anti‐αGal‐Abs also exist as IgA and IgG in milk, colostrum, saliva, and bile 38 . Thus, anti‐αGal‐Abs are the most suitable for human AGA LUVs 12,36‐53 …”
Section: Safety Mechanismsmentioning
confidence: 99%
“…It has been found that anti‐αGal‐Abs can aid complements to destroy over ten species of viruses carrying αGal‐Gs, 36,42‐48 and aid immune cells to kill HIV‐1 through ADCC and ADCP 49 . Multiple studies demonstrated that anti‐αGal‐Abs could even aid immune cells to kill cancer cells and play a key role in rejecting xenografts carrying αGal‐Gs through ADCC 36,50 …”
Section: Safety Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation